Investigation on different composition of powder metallurgy electrode (Cu-W) in high performance edm (HPEDM) on AISI D2 hardened steel - Abdul Hamid, Faizul Ezmat (2013)
The ideal selection of manufacturing conditions is one of the most important aspects to take into consideration in the majority of manufacturing processes and particularly in processes related to Electrical Discharge Machining (EDM). EDM die sinking machines are used to machine conductive metals of any hardness or difficult to machine with traditional methods. The problem in the capabilities of tool electrodes which are not utilized at the optimum levels of the operating parameters has attracted the attention of researchers and practicing engineers to manufacture tool electrodes with highly great performance. In this work, an experimental design was conducted to characterize the machining performances and surface integrity of three different composition of copper tungsten (CuW) tool electrode in EDM of D2 hardened steel (58-62 HRC). Machining performances i.e. material removal rate (MRR), tool wear rate (TWR), workpiece surface roughness (Ra) and micro-hardness (MH) were studied for the three different composition of CuW tool electrode made through powder metallurgy (PM) method. Machining variables were peak current and pulse duration, meanwhile machining voltage, depth of cut and duty factor were kept constant. The 65%W electrode is the best choice of CuW electrode on machining D2 hardened steel due to the highest machining rate, reasonable tool wear rate and acceptable surface characteristics. The improvement of MRR is obviously affected by the increment of current intensity. MRR increased as the value of peak current increased. The increment of pulse duration is not essentially improving MRR. There is no clear relation between the alteration of pulse duration and MRR. However, the MRR becomes the optimum at an optimal set of variables which is set at 40A and 400µs. The results of the machining performance can extent the availability of database on EDM machinability and surface characteristics of D2 hardened steel for machinist practices in industrial application of roughing operation.